2014
DOI: 10.1586/14779072.2014.902309
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–lymphocyte ratio as an important assessment tool

Abstract: Response to: Akhtar MS, Bhat T, Teli S et al. Neutrophil to lymphocyte ratio and cardiovascular diseases: a review. Expert Rev. Cardiovasc. Ther. 11(1), 55-59 (2013).We read the article 'Neutrophil to lymphocyte ratio (NLR) and cardiovascular diseases: a review' by MS. Akhtar et al. with great interest [1]. In this wellpresented review, the authors discussed the association of N/L ratio with various cardiovascular diseases and its possibility of emerging as a cheap, reliable and independent prognostic marker o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 7 publications
2
31
0
1
Order By: Relevance
“…41 Our results also show that percentile distribution of NLR associates with progressive subclinical atherogenesis, as measured by CIMT. This is consistent with previous studies, which postulate that NLR is related to endothelial dysfunction, 33 atherosclerosis and inflammatory disorders like Behcet's disease, 42 as well as its role as predictor of coronary subclinical calcification, 8,43 severity of the atherogenic injury, either in coronary or peripheral artery disease 44 or independent association with severe multi-level peripheral artery disease. 26,45 Indeed, there is experimental evidence that the accumulation of neutrophils on the vascular wall might promote inflammation, endothelial dysfunction and atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…41 Our results also show that percentile distribution of NLR associates with progressive subclinical atherogenesis, as measured by CIMT. This is consistent with previous studies, which postulate that NLR is related to endothelial dysfunction, 33 atherosclerosis and inflammatory disorders like Behcet's disease, 42 as well as its role as predictor of coronary subclinical calcification, 8,43 severity of the atherogenic injury, either in coronary or peripheral artery disease 44 or independent association with severe multi-level peripheral artery disease. 26,45 Indeed, there is experimental evidence that the accumulation of neutrophils on the vascular wall might promote inflammation, endothelial dysfunction and atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
“…3,4 Moreover, early leucocyte recruitment is known to be closely associated with vascular endothelial dysfunction. [5][6][7] Immune cells are involved from earliest fatty streaks to late-stage complex vascular plaques, 5,8 where neutrophils play a role in the progression of atherogenesis and atherosclerosis. 9,10 Invasion and local activation of neutrophils in the atherosclerotic plaque have been evidenced by direct visualization with consequent triggering of atherogenic process.…”
mentioning
confidence: 99%
“…In addition, according to our results, in a study carried out in 26,016 middle-aged and older adults (>35 years old) with metabolic syndrome in Taiwan, obesity, high body fat, high WC or hip circumference, and high WHtR were significantly associated with increased odds ratios of high CRP and NLR [12]. Furthermore, some studies in obese adults showed that weight loss improved inflammation parameters [91,92]. Nevertheless, in some previous studies, increased BMI was associated with total WBC and individual subtypes, but not with NLR [92][93][94].…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, some studies in obese adults showed that weight loss improved inflammation parameters [91,92]. Nevertheless, in some previous studies, increased BMI was associated with total WBC and individual subtypes, but not with NLR [92][93][94]. More research is needed to clarify this relationship.…”
Section: Discussionmentioning
confidence: 95%
“…Even patients with increase NLR but normal TLC count could have increased risk of atherosclerosis related diseases. [12][13][14] HbA1c is commonly advised to measure the long term glycemic control and it also tells about the severity of hyperglycemia. 15 However HbA1c usually do not predict ongoing inflammation and diabetes associated complications accurately.…”
Section: Figure 4: Comparison Of Nlr Among Three Groupsmentioning
confidence: 99%